Exploring Illocutionary Acts in The Film a Star Is Born (2018): a Pragmatics Study - Leirisya Agni Al Zahra; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2025)
Previous studies on speech acts in films have mainly focused on classification, with limited attention to their role in constructing emotional meaning and interpersonal relationships. Therefore, this study aims to identify the types of illocutionary acts used by the main characters in the film A Star is Born (2018) and to analyze their communicative purpose based on Searle’s (1985) classification, particularly in relation to character development and emotional dynamics. A total ofeleven utterances were selected and categorized into four types of illocutionary acts: assertive, directive, commissive, and expressive. Declarative acts were not found due to the absence of institutional context within the narrative. The researcher used a descriptive qualitative method to select eleven utterances as representative data to answer two research questions about the types and functions of the utterances used. The findings show that assertive acts are the most dominant type, primarily used to express beliefs, personal experiences, and emotional states, thereby contributing to the development of mutual understanding between characters. Directive acts function to influence actions and encourage decision-making, often appearing in moments of tension or support. Commissive acts reflect commitments that strengthen trust, while expressive acts convey emotions such as love, pride, and sadness, reinforcing emotional intimacy. Overall, illocutionary acts play a crucial role in shaping character relationships and driving emotional development within the fil’s narrative. By providing an understanding of how language can provide meaning in written conversations while evoking emotional feelings, this research is expected to contribute to the field of pragmatics and media discourse.